629 Enhancing paediatric undergraduate teaching through simulation – reflections and insights. (17th August 2022) - Tan, Sapphire; Schofield, Laurel; Natasha, G; Prentice, Sarah; Ahmed, Syed Ather; Kagalwala, Fatima
Abstract : Aims: Opportunities for medical students to be involved in managing acutely unwell paediatric patients are limited owing to their relatively short undergraduate paediatric placements, as well as the infrequent nature of such events. Simulation-based education (SBE) plays an increasingly important role in paediatric medical education, as it provides more opportunities for students to gain experience, confidence and competence in managing such scenarios in a safe environment. We aimed to evaluate and enhance paediatric undergraduate teaching through SBE on various acute paediatric scenarios delivered at a single district general hospital. Methods: We conducted low-fidelity SBE sessions on various realistic acute paediatric scenarios for Year 5 medical students from University College London on their paediatric placement at Lister Hospital (Stevenage). This included a debrief period at the end of the scenario to provide students with individualised feedback and enable them to consolidate their learning. Pre- and post-session feedback were collated from students to evaluate the effectiveness of the teaching and highlight any areas for improvement. Results: We conducted 3 SBE sessions between September 2019 and February 2020. Pre- and post- session feedback were obtained from 10 students. Pre-session feedback identified several intended learning objective themes ( figure 1 ). The most common learning objective theme was to gain more experience in managing acute emergencies. Another popular theme was developing non-technical skills including: team-working, leadership skills, communication with the multidisciplinary team and parents, and situational awareness. Other objectives that were mentioned include understanding the similarities/differences between paediatric and adult care and being more familiar with paediatric equipment. Post-session feedback was very positive: 100% (10/10) of students felt that the simulation and debrief provided a valuable learning experience, and that they would recommend this simulation to others. Qualitative feedback identified several actual learning outcomes which were analysed and mapped to the themes of their intended learning objectives (table 1). Overall, students reported that the acute management of paediatric emergencies and developing interpersonal skills were well covered in the session. Interestingly, a particularly popular sub-theme within development of non-technical skills was communicating with parents – 40% (4/10) of students mentioned this in their actual learning outcomes, even though it was only mentioned by 10% (1/10) of students in the intended learning objectives. There was no mention of learning about the similarities/differences between paediatric and adult care and about using paediatric equipment, identifying possible room for improvement. Other suggestions for improvement included 'more theory', better 'usage of equipment to improve realism' and having more 'time for all of [the students] to practice'. Conclusion: Reflections from our local SBE sessions were very positive as indicated by student feedback, enabling undergraduate students to gain exposure in managing acute paediatrics scenarios in a safe environment. It was particularly encouraging to discover even low-fidelity sim benefits student experience. Opportunities for areas of improvement, for example creating more scenarios involving parental communication, were also highlighted. Our study demonstrates the benefits of simulation for undergraduate students, particularly in their learning of both technical and non-technical skills, whilst on their paediatric placement.